ChemInform Abstract: Direct Amidation of Carboxylic Acids Catalyzed by ortho‐Iodo Arylboronic Acids: Catalyst Optimization, Scope, and Preliminary Mechanistic Study Supporting a Peculiar Halogen Acceleration Effect. Issue 5 (13th February 2013) - Gernigon, Nicolas; Al‐Zoubi, Read M.; Hall, Dennis G.
Abstract The ortho‐iodo arylboronic acid shown in the scheme efficiently promotes the direct amidation of carboxylic acids, which allows convenient formation of a wide range of carboxylic amides.